Kebijakan Hukum Pidana Kurungan sebagai Pengganti Pidana Denda dalam Perkara Tindak Pidana Korupsi - Nur Habib Auliya; Setiyono Setiyono (MLJ Merdeka Law Journal, 2021)
This article aims to examine and analyze the regulation of fines in the Anti-Corruption Law, and future legislative policies regarding imprisonment as a substitute for fines in corruption cases. This research includes normative legal research (doctrinal) with a legal approach. The results show that the policy of determining the amount of fines clearly deviates from the policy of the Criminal Code as its parent law, both in terms of the number/size which has increased many times, as well as the adoption of a Special Minimum System in addition to a Special Maximum. In terms of determining the amount of fines contained in various special crimes in the laws and regulations in Indonesia, one of which is the Anti-Corruption Law which turns out to show a pattern of formulating the amount of fines that is different (inconsistent) with each other. Legislative policy regarding imprisonment as a substitute for fines in future corruption cases can be pursued by formulating criminal law as in the RKUHP in the form of the convict not paying the fine imposed on him, then he is subject to the taking of assets or the convict's opinion in accordance with the criminal law.DOI: https://doi.org/10.26905/mlj.v2i2.7159